2022
DOI: 10.3390/ijms23073425
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Ischemia/Reperfusion-Induced Alterations in Subcellular Organelles by Ischemic Preconditioning

Abstract: It is now well established that ischemia/reperfusion (I/R) injury is associated with the compromised recovery of cardiac contractile function. Such an adverse effect of I/R injury in the heart is attributed to the development of oxidative stress and intracellular Ca2+-overload, which are known to induce remodeling of subcellular organelles such as sarcolemma, sarcoplasmic reticulum, mitochondria and myofibrils. However, repeated episodes of brief periods of ischemia followed by reperfusion or ischemic precondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 214 publications
(251 reference statements)
0
16
0
Order By: Relevance
“…In order to attenuate the adverse effects of oxidative/nitrosative stress, inflammation and intracellular Ca 2+ -overload in I/R hearts, different redox-based strategies involving endogenous components have been attempted to prevent I/R-induced myocardial cell damage and cardiac dysfunction [ 77 , 78 , 79 ]. Particularly, interventions such as ischemic preconditioning, ischemic postconditioning, and remote conditioning have been demonstrated to exert cardioprotective actions in improving cardiac performance as well as limiting infarct size and preventing adverse cardiac remodeling due to I/R injury [ 80 , 81 , 82 ]. It is pointed out that there are several other conditions such as hibernation of myocardium and early stages of myocardial ischemia but their cardioprotective effects against I/R injury have not been examined in details.…”
Section: Cardioprotection In Hearts Subjected To I/r Injurymentioning
confidence: 99%
“…In order to attenuate the adverse effects of oxidative/nitrosative stress, inflammation and intracellular Ca 2+ -overload in I/R hearts, different redox-based strategies involving endogenous components have been attempted to prevent I/R-induced myocardial cell damage and cardiac dysfunction [ 77 , 78 , 79 ]. Particularly, interventions such as ischemic preconditioning, ischemic postconditioning, and remote conditioning have been demonstrated to exert cardioprotective actions in improving cardiac performance as well as limiting infarct size and preventing adverse cardiac remodeling due to I/R injury [ 80 , 81 , 82 ]. It is pointed out that there are several other conditions such as hibernation of myocardium and early stages of myocardial ischemia but their cardioprotective effects against I/R injury have not been examined in details.…”
Section: Cardioprotection In Hearts Subjected To I/r Injurymentioning
confidence: 99%
“…Indeed, our previous studies found that high doses of NE could further induce mitochondrial fragmentation by disrupting actin. Some studies also showed that sustained high NE levels led to decreased mitochondrial calcium uptake and increased intracytoplasmic calcium concentration ( Gutiérrez et al, 2014 ), then the communication and proximity between SR/ER and mitochondria were changed ( Tappia et al, 2022 ). That may be the reason why 0.5 μg/kg/min did not significantly attenuate mitochondrial damage induced by UHS.…”
Section: Discussionmentioning
confidence: 99%
“…IPC is con rmed to be a safe and e cient method with potential protective effect on organs recently [22].…”
Section: Discussionmentioning
confidence: 99%